PENGARUH MODEL PROTECTION MOTIVATION TERHADAP KEPATUHAN PENGGUNAAN ALAT PELINDUNG DIRI PADA TENAGA KESEHATAN GIGI DI RS SURABAYA - Silvia Prasetyowati; Supriyana -; Irma H.Y. Siregar; Oni Setiani (Jurusan Keperawatan Gigi Poltekkes kemenkes Denpasar, 2015)
Background : Health workers protection with themselves in order not to infected the disease must use of personal protective equipment such as masks, gloves, face shield, and lab coot. Prevention of infected towards HIV/AIDS accompanied by protective glasses, hair coverings, and plastic disposable protection. Model of protection motivation theory is one of behavior changing model used to motivate dental health towards compliance using personal protective equipment , with four factors concept such as threat, susceptible, ffictiveness of response, and confidence, when there is danger/problems and the actions of individuals will change.Research Purposes : To prove model of protection motivation on dental health towards compliance using personol protective equipment during dental treatment at Dental Poly.Research Method :This research is a Quasi experiments with design one group pretest- post test. This design not use control but do observations on the dependent variable. Number of respondent 56 people. Data analysis according to wilcoxon match in the dependent t-test.Research result : The result of this study it can be concluded that There are differences in perception between the values before and after the intervention model of protection motivation with significant value : 0.001 p (P-value 0.05), and differences in compliance value using personal protective equipmet (masks, gloves, apron, face shield) before and after a motivotional training Protection models with signifcant value : 0.001 p (p-value 0,05).Conclusion : There was effect to compliaance model of protection motivation using of personal protective equipment on dental nurse.